Winter activity of the snake-eyed lizard Ophisops elegans (Reptilia: Lacertidae) in the northwesternmost part of its range - Georgi Krastev; Emiliya Vacheva; Borislav Naumov (Historia naturalis bulgarica, 2023)
There is a lack of information for potential winter activity of the snake-eyed lizard Ophisops elegans in Europe, where it has a limited distribution. To test the hypothesis that this species can be active during the winter months, two locations in Bulgaria were chosen. The visits were conducted in January, February and December 2022 near the village of Meden Buk and in December 2022 above the village of Mezek. A total of 19 individuals of O. elegans were recorded. In addition, we confirmed foraging behaviour based on faecal sample collection. To our knowledge, this is the northernmost record of winter activity in the snake-eyed lizard and the first consecutive observation of year-round activity for this species in Europe.